An outlook: parking space in the federal administration centre of Putrajaya / Irmawati Abdul Majid - Abdul Majid, Irmawati (2010)
The growth and development of Putrajaya as the Federal Administration Centre has caused its traffic system to develop so rapidly in such a way that the demand for parking space increases tremendously. The traffic condition in Putrajaya, especially during office hours, has become congested and affects the quality of life—socially, economically and environmentally. The rapid increase in Putrajaya population, especially since 2005 when thousands of government employees were asked to relocate to Putrajaya in a centralized exercise, a steady stream of complaints about the lack of parking space began to arise. Most people who work in Putrajaya, customers who deal with the government offices and the visitors to Putrajaya complained about the hassles in finding parking space for their vehicles. Most of the times, especially during office hours, many vehicles are found parked illegally along roadside, road shoulders, bus stop areas and other undesignated areas near Complex A, B, C, D and E in Precinct 1. Therefore, the main objective of this project is to identify the key factor that causes parking problem in Putrajaya. Apart from the main objective, this study also try to assess the public perception towards the implementation of total public transportation services in Putrajaya; to find out whether the measures taken by the Putrajaya Corporation, in improving the public transportation services, have been effective; and to provide recommendations of improvement in order to allow Putrajaya to meet the access and parking requirements of its residents, visitors, shoppers and traders, and therefore be an attractive place to visit, work and live.